Evaluation of deep penetration of high-temperature sustained-release acid based on the reaction kinetics and conductivity of acid-etched fractures. (October 2022) - Sui, Yu; Cao, Guangsheng; Guo, Tianyue; Zhang, Zihang; Bai, Yujie; Wu, Jiajun; Yao, Liming
Abstract: Aiming at improving the acid fracturing effect of carbonate reservoirs at high temperatures, reaction kinetics and acid fracture conductivity of five high-temperature sustained-release acids were investigated. The experimental results show that viscous acid, gelled acid II, authigenic acid I, and gelled acid I have the highest rate constant, respectively. It was found that as the temperature increases, the reaction order of gelled acid I, viscous acid, and authigenic acid II decreases, while the reaction order of gelled acid II and authigenic acid I increase first and then decreases. Among the studied cases, the maximum reaction rate is 4.46 × 10 −5  mol/(L·s), which was achieved in gelled acid I. Variations of the reaction rate indicate that gelled acid I is in the "saturation state of the reaction''. At a closing pressure of 40 MPa and a temperature of 150 °C, the acid corrosion fracture conductivity of gelled acid I is the largest, reaching 7.45 × 10 −2  μm 2  m, the fracture conductivity of authigenic acid I was higher than that of autogenic acid II, and the conductivity of the viscous acid was the lowest.